Computer-aided drug design guided by hydrogen/deuterium exchange mass spectrometry: A powerful combination for the development of potent and selective inhibitors of Group VIA calcium-independent phospholipase A2. Issue 20 (15th October 2016) - Mouchlis, Varnavas D.; Morisseau, Christophe; Hammock, Bruce D.; Li, Sheng; McCammon, J. Andrew; Dennis, Edward A.
Graphical abstract: Abstract: Potent and selective inhibitors for phospholipases A2 (PLA2 ) are useful for studying their intracellular functions. PLA2 enzymes liberate arachidonic acid from phospholipids activating eicosanoid pathways that involve cyclooxygenase (COX) and lipoxygenase (LOX) leading to inflammation. Anti-inflammatory drugs target COX and LOX; thus, PLA2 can also be targeted to diminish inflammation at an earlier stage in the process. This paper describes the employment of enzymatic assays, hydrogen/deuterium exchange mass spectrometry (DXMS) and computational chemistry to develop PLA2 inhibitors. Beta-thioether trifluoromethylketones (TFKs) were screened against human GVIA calcium-independent, GIVA cytosolic and GV secreted PLA2 s. These compounds exhibited inhibition toward Group VIA calcium-independent PLA2 (GVIA iPLA2 ), with the most potent and selective inhibitor3 (OTFP ) obtaining an X I (50) of 0.0002 mole fraction (IC50 of 110 nM). DXMS binding experiments in the presence ofOTFP revealed the peptide regions of GVIA iPLA2 that interact with the inhibitor. Molecular docking and dynamics simulations in the presence of a membrane were guided by the DXMS data in order to identify the binding mode ofOTFP . Clustering analysis showed the binding mode ofOTFP that occupied 70% of the binding modes occurring during the simulation. The resulted 3D complex was used for docking studies and a structure–activity relationship (SAR) was established. This paper describes a novel multidisciplinary approach in which a 3D complex of GVIA iPLA2 with an inhibitor is reported and validated by experimental data. The SAR showed that the sulfur atom is vital for the potency of beta-thioether analogues, while the hydrophobic chain is important for selectivity. This work constitutes the foundation for further design, synthesis and inhibition studies in order to develop new beta-thioether analogues that are potent and selective for GVIA iPLA2 exclusively.